IMPLEMENTASI MANAJEMEN KESISWAAN DALAM MENINGKATKAN PRESTASI NON AKADEMIK DI SDIT ASH SHOHWAH TANJUNG REDEB - Ahmad Syaddad (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
This research aims to find out: (1) how student management is implemented at SDIT Ash Shohwah Tanjung Redeb; (2) student management efforts to improve the non-academic achievements of SDIT Ash Shohwah Tanjung Redeb students; (3) supporting and inhibiting factors in implementing student management at SDIT Ash Shohwah Tanjung Redeb. This research is qualitative research with data collection methods carried out by interviews, observation and documentation. Qualitative data is analyzed through identifying data, classifying data, analyzing data, and concluding data. The results of this research show that student management organizes students improve non-academic achievements starting from student planning, student acceptance, student organizing, student orientation, student attendance. Student coaching and services, student organizations, student assessment, transfers and student alumni. Student management effots to improve students non-academic achievements include planning students non-academic achievements, grouping students according to their chosen talents and interests, and developing non-academic achievements well. The supporting factors for student management in improving the non-academic achievements of SDIT Ash Shohwah Tanjung Redeb students are divided into two, namely encouragement from within (attitude towards learning, motivation to learn, concentration, saving learning results, self-confidence, intelligence, habits and aspirations of students) and encouragement from outside (parents, teachers or coaches, facilities and infrastructure, social environment), while the inhibiting factor is limited time due to the large number of student activities at school.